Improving the Effectiveness of FDA Drug Inspection - Klimberg, Ronald; Revelle, Charles; Cohon, Jared (Operations research, 1992)
The evaluation and the allocation of inspection resources is a problem faced by private sector firms as well as by several government agencies. This paper reports the development and the use by the Food and Drug Administration (FDA) of decision making tools for measuring the performance of their drug inspection activities in which data are collected only intermittently, and a multiobjective integer program to assist FDA decision makers in planning and evaluating the effectiveness of their drug inspection activities.